2017
DOI: 10.1111/mmi.13658
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lysine acetylation of a phosphoenolpyruvate carboxylase involved in glutamate overproduction in Corynebacterium glutamicum

Abstract: Protein Nε-acylation is emerging as a ubiquitous post-translational modification. In Corynebacterium glutamicum, which is utilized for industrial production of l-glutamate, the levels of protein acetylation and succinylation change drastically under the conditions that induce glutamate overproduction. Here, the acylation of phosphoenolpyruvate carboxylase (PEPC), an anaplerotic enzyme that supplies oxaloacetate for glutamate overproduction was characterized. It was shown that acetylation of PEPC at lysine 653 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…6) It is likely that in the L-glutamate-producing conditions, a large portion of the carbon flux is shifted toward the anaplerotic pathway mediated by phosphoenolpyruvate carboxylase, rather than the acetyl phosphate and acetate-producing Pta-AckA pathways, with the resulting depletion of acetylation substrates. 6,7) In this condition, succinylation utilizing succinyl-CoA would readily occur. Although we have not identified an enzyme responsible for K132 succinylation, a non-enzymatic mechanism might be considered, as suggested in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) It is likely that in the L-glutamate-producing conditions, a large portion of the carbon flux is shifted toward the anaplerotic pathway mediated by phosphoenolpyruvate carboxylase, rather than the acetyl phosphate and acetate-producing Pta-AckA pathways, with the resulting depletion of acetylation substrates. 6,7) In this condition, succinylation utilizing succinyl-CoA would readily occur. Although we have not identified an enzyme responsible for K132 succinylation, a non-enzymatic mechanism might be considered, as suggested in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…6) We also showed that phosphoenolpyruvate carboxylase, which is an anaplerotic enzyme catalyzing the supply of oxaloacetate and which is essential for L-glutamate production, is regulated by protein acetylation. 7) However, the functions of acylation of most other proteins remain to be elucidated.…”
mentioning
confidence: 99%
“…It is now clear that the extent of acetylation, the mechanisms by which acetylation occurs, the identities of acetylated proteins, and the locations of acetylation on those proteins can vary between organisms; yet, in most cases, there is great conservation in core cellular processes (Nakayasu et al, 2017). Such approaches have shown that acetylation occurs on proteins involved in a wide diversity of cellular process, especially central metabolism and translation (Wang et al, 2010; Weinert et al, 2013a; Baeza et al, 2014; Kuhn et al, 2014; Kosono et al, 2015; Schilling et al, 2015; Kentache et al, 2016; Birhanu et al, 2017; Jers et al, 2017; Nagano-Shoji et al, 2017; Post et al, 2017; Bontemps-Gallo et al, 2018; Gaviard et al, 2018; Sun et al, 2018; Vasileva et al, 2018; Yoshida et al, 2019). As stated above, many of these acetylations are conserved.…”
Section: Mass Spectrometry-based Proteomics To Study Bacterial Acetylmentioning
confidence: 99%
“…Phosphoenolpyruvate and carbon dioxide synthesize oxaloacetic acid under the catalysis of PEPC, and then oxaloacetic acid enters the TCA cycle for further metabolism. The expression and activity of PEPC affects the synthesis of glutamic acid in C. glutamicum [46,47] . Lysine at position 653 (K653) is essential for the regulation of PEPC acetylation.…”
Section: Effect Of Modi Cation Of Phosphoenolpyruvate Carboxylase On mentioning
confidence: 99%
“…found that acetylation of PEPC at K653 could decrease enzymatic activity and glutamate production, which refer to the K653-acetylation could regulate PEPC activity negatively. Mutated K653 into arginine could decrease the level of acetylation on PEPC, which correspondingly improve its activity [47] . In addition, PEPC would be feedback suppressed by aspartic acid when it was overexpressed in C. glutamicum.…”
Section: Effect Of Modi Cation Of Phosphoenolpyruvate Carboxylase On mentioning
confidence: 99%